MENGENAL BLENDED LEARNING - M. Yusuf T. (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2011)
Learning model will go on developing in line with the innovation of technology of education. The traditional learning model will be left behind in order to keep up with students demand. The Blended Learning model is one of the models that may answer the de-mand of education technology. Terminologically, Blended Learning is relatively new to a higher education, even in a company. Despite this, Blended Learning is a combination of a number of models or teaching methods. This paper will deeply discuss the definition, strengths and weaknesses, the development and some obstacles of this model.